Jump into JMP Scripting - Murphrey, Wendy; Lucas, Rosemary (SAS Institute, 2018)
Learn the essentials of the JMP Scripting Language with this beginner's guide. Written in an easy-to-understand style based on the authors' extensive experience, Jump into JMP Scripting, Second Edition teaches beginner scripters how to take advantage of the robust JMP Scripting Language (JSL) using step-by-step instructions and real-world situations. The authors demonstrate how JSL offers the freedom to create scripts from the very simple and specific to the most generic and complex. With a new chapter on JSL language foundations, the first half of the book explains the fundamentals of JSL and.